ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICAL STUDY OF VERNONIA GLABRA (STEETZ) OLIV. & HIERN. IN KENYA. - Kitonde, Kadogo Kadogo; Fidahusein, Dossaji Saifuddin; Lukhoba, Catherine Wanjiru; Jumba, Miriam Musamia (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Infectious diseases are prevalent and life threatening in Kenya. Majority of the sick are seeking herbal remedies in search of effective, safe, and affordable cure. This project aims to investigate the antimicrobial activity and presence of active phytochemical compounds in different parts of Vernonia glabra; a plant used by herbalists in various regions of Kenya, for the treatment of gastrointestinal problems. The plant sample was collected in January 2010 in Machakos, and different parts dried at room temperature under shade, ground into powder and extracted in Dichloromethane: Methanol in the ratio 1:1, and water. These crude extracts were tested against Staphylococcus aureus, Escherichia coli, Candida albicans, and Aspergillus niger for antimicrobial activity using disc diffusion technique. Minimum inhibitory concentrations (MICs) for active crude extracts were done using disc diffusion technique after the failure of agar and broth dilution methods. It was observed that the organic crude extracts of flower, leaf, stem, root, and/or entire plant, showed activity against at least one of the four micro-organisms screened, and at concentrations lower than the aqueous crude extracts. Organic crude extract of the leaf showed the highest activity against Staphylococcus aureus (mean inhibition zone of 1.85), recording higher activity than the commercially used standard antibiotic (Streptomycin mean inhibition zone of 1.30). The organic crude extract of flower showed significant activity only against S. aureus, with the lowest MIC of 1.5625 mg/100µl, compared to streptomycin with M.I.C of 6.25 mg/100µl. Thin Layer Chromatography-Bioautography Agar-Overlay showed that, flower alkaloids (50% active), root sapogenins (43.8% active), and root terpenoids (38.5% active) were identified as the potential antibacterial compounds against S. aureus. These results suggest that, V. glabra contains phytochemicals of medicinal properties and justify the use of V. glabra in traditional herbal medicine for the treatment of microbial based diseases. However, research on toxicity which is missing in this study is recommended for V. glabra in order to verify, validate and document the safety of this medicinal plant to the society.